A clinicopathological study and management of odontogenic keratocyst - Rahman, Mohammad Asifur; Rahman, Tarin; Haider, Ismat Ara (Update Dental College Journal, 2019)
Odontogenic Keratocyst is an aggressive odontogenic cyst with a high recurrence rate. After radicular and follicular cysts, odontogenic keratocysts are the third most common cyst of the jaws and approximately 12-14% of all odontogenic cysts. It has been retermed to Keratocystic odontogenic tumour (KCOT) as it better reflects its neoplastic nature but recently it has been re classified and retermed into the cystic category. Various surgical methods have been proposed but comparatively, conservative treatment options such as Dredging methods might be the treatment of choice due to preservation of anatomical structure. Objective: The aim of this study was to analyse the clinical, radiological and histopathological characteristics of Odontogenic Keratocyst and provide a proper management system affected by this type of lesions. Materials and methods: The prospective study was performed in Dhaka Dental College and Hospital from a period of January 2014 to January 2018. A total number of 75 patients were selected for this study based on clinical, radiological and histopathological confirmation of odontogenic keratocysts. The treatment options were enucleation, enucleation with curettage, enucleation with peripheral ostectomy, Dredging method and surgical resection. After treatment patients were followed up 1months, 3 months and 6 months in every year at least for 5 years. Results: Among 75 patient of odontogenic keratocyst; the mean age was 27.69±13.35 and age range was 11 to 66 years. Male were 53(71%) and 22 (29%) were female patients. 53 (70.67%) cases were found in the mandible, 15(20%) cases in the maxilla and in 7(9.33%) cases were involved in both maxilla and mandible; mandibular posterior region was the most specific region involved 37(69.81%).The most common clinical features revealed pain and swelling. Radiologically, 70.66% unilocular, 96% well defined and 94.66% radiolucent area were prominent. Bone expansion 37.38%, root resorption 30.00% and 36% were associated with an impacted tooth. Regarding treatment options enucleation with curatage 12%, enucleation, curettage & peripheral ostectomy 29.33%, Dredging 52% and surgical resection 6.6% was done. Recurrence occurred in 18 patients with recurrence rate of 24%. Conclusion: Odontogenic keratocyst is an aggressive cyst, male predominant, posterior mandible is the commonest site and well defined unilocular radiolucency are commonest radiological feature. Radical treatment options such as resection reduced the recurrences of the tumour but higher morbidity and jaw deformity. Comparatively, conservative treatment options such as Dredging methods might be the treatment of choice due to preservation of anatomical structure. A long term follow up is paramount importance for the research and understanding the clinical pattern, behavior, treatment and recurrence of the lesion. Update Dent. Coll. j: 2019; 9 (1): 8-15